STRATEGI PROMOSI DIGITAL MARKETING WISATA RAFTING GUNA MENINGKATKAN POTENSI DESA WISATA - Dewi Diah Fakhriyyah; Daimatul Munawaroh; Diah Utami; Dita putri; Fadhila Khoirun Nisa'; Fadhila Nur Khaliza; Fandi Ahmad; Farradina Farradina; Ferlika Ferlika; Jacky Jaffan; Muhammad Maimun; Muhammad Mudzakir (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2022)
Banyu Rancang Rafting Tour which is located in Torongrejo Village, Batu City is experiencing problems in promoting tourism. This is the background for conducting socialization activities and marketing practices both through print and digital marketing media. Activities are carried out using socialization, training and mentoring methods. The socialization material is about digital marketing which is currently a trend to expand market potential. Then the training is carried out by practicing making banner designs and tourism promotion brochures which can later be printed and can also be uploaded on social media. Next is to create a Tiktok social media account and create video content to be uploaded on Tiktok social media accounts, as well as Facebook and Instagram that have been previously owned. The result of this activity is the addition of social media accounts from Banyu Rancang Rafting, namely Tiktok accounts, tourism promotional content videos, brochures both printed and online, as well as banners installed in various strategic places.